Pengembangan Media Pembelajaran Macromedia Flash Berbasis Saintifik - Agustan Ependi; Lucy Asri Purwasi; Idul Adha (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to develop scientific-based macromedia flash learning media on integer material for seventh grade junior high school students and determine the quality of learning media developed based on validity and practicality. This research is a development study using the ADDIE development model. The stages of the ADDIE development model consist of 5 stages, namely: Analysis, Design, Development, Implementation, Evaluation. The results of the study, from the results of the assessment analysis by the three experts namely: linguists, material experts, and media experts, the learning media developed met very valid criteria with an average score of 4.24. The results of the analysis of the practicality of the user questionnaire (teachers and students) met very practical criteria with an average score of 4.37. The characteristics of the developed media are 1) The material is in accordance with the competency to be achieved; 2) The learning objectives are clear; 3) There are clear instructions; 4) Language that is easily understood by students; 5) In accordance with the approach used is a scientific approach; 6) There is a section to motivate students; 7) Clear learning flow; 8) There are practice questions and discussion as well as evaluation questions; 9) Interactive; 10) Easy navigation; 11) Images, animations, text, and colors are presented in harmony and harmony. In conclusion, the development of scientific-based macromedia flash learning media meets valid and practical criteria for use by VII grade junior high school students in learning integer material. Keywords: Integer, Macromedia Flash, Scientific, Development of Learning Media